Development and validation of a new Multidisciplinary Approach Competency Scale for Prevention of Child Abuse from Pregnancy (MUSCAT). - Chika Sakakida; Etsuko Tadaka; Azusa Arimoto (PLoS ONE)
Child abuse remains a major global problem. A high-quality multidisciplinary approach involving different professionals for the early prevention of child abuse beginning from pregnancy is paramount because child abuse is associated with multiple potential risk factors at individual and societal levels. A multidisciplinary approach to preventing child abuse involves interprofessional coordination, and requires clear definitions of professional competency. However, no scale to measure professional competency for such multidisciplinary approaches is available. This study aimed to develop and validate the Multidisciplinary Approach Competency Scale for Prevention of Child Abuse from Pregnancy (MUSCAT). First, a draft scale comprising 30 items was developed based on a literature review, and then refined to 21 items through expert interviews. Next, a cross-sectional survey was conducted among experts from 1,146 child and maternal health institutions (health centers, perinatal medical centers/hospitals, child consultation centers, midwife clinics, and kindergartens) in 10 major prefectures and cities throughout Japan. The questionnaire collected respondents' demographic data and information about one child abuse case, and asked respondents to apply the provisional MUSCAT to the reported case. Finally, three of the 21 items were excluded by item analysis, leaving 18 items for exploratory factor analysis. Confirmatory factor analyses identified 10 items on two factors: "Collaborative Networking" and "Professional Commitment." The goodness of fit index was 0.963, adjusted goodness of fit index was 0.939, comparative fit index was 0.988, and root mean square error of approximation was 0.043. The Cronbach's alpha for the entire scale was 0.903, and values for the subscales were 0.840-0.875. The overall scale score was positively correlated with the Interprofessional Collaboration Competency Scale. The MUSCAT demonstrated acceptable internal consistency and validity, and has potential for use in advancing individual practice and team performance in multidisciplinary approaches for early prevention of child abuse.